International handbook of the demography of poverty and inequality - Singelmann, Joachim; Poston, Dudley L., 1940- (International handbooks of population, 2025)
This handbook provides a comprehensive and comparative review of poverty and inequality in developing and developed countries from demographic, sociological, and political perspectives. It discusses the basics of poverty and inequality, issues among race/ethnic and sexual minority subpopulations, social processes, country and comparative perspectives, child poverty, and anti-poverty policies. It also touches on regional disparities, noting rapid declines in poverty in China and South Asia, but increases in some Sub-Saharan African countries. The handbook serves as a valuable reference for demographers, social scientists, policy makers, and NGOs.